Opportunistic disease in yellow perch in response to decadal changes in the chemistry of oil sands-affected waters. (March 2018) - Hogan, Natacha S.; Thorpe, Karen L.; van den Heuvel, Michael R.
Abstract: Oil sands-affected water from mining must eventually be incorporated into the reclaimed landscape or treated and released. However, this material contains petrogenic organic compounds, such as naphthenic acids and traces of polycyclic aromatic hydrocarbons. This has raised concerns for impacts of oil sands process-affected waters on the heath of wildlife and humans downstream of receiving environments. The objective of this study was to evaluate the temporal association of disease states in fish with water chemistry of oil sands-affected waters over more than a decade and determine the pathogens associated with disease pathologies. Yellow perch ( Perca flavescens ) captured from nearby lakes were stocked into two experimental ponds during 1995–1997 and 2008–2010. South Bison Pond is a drainage basin that has received unextracted oil sands-contaminated material. Demonstration Pond is a constructed pond containing mature fine tailings capped with fresh water. Two disease pathologies, fin erosion for which a suspected bacterial pathogen ( Acinetobacter Iwoffi ) is identified, and lymphocystis (confirmed using a real-time PCR) were associated with oil sands-affected water exposure. From 1995 to 1997 pathologies were most prevalent in the South Bison Pond; however, from 2008 to 2009, disease was more frequently observed in the Demonstration Pond. CYP1A activity was 3–16 fold higher in fish from experimental ponds as compared to reference populations and this pattern was consistent across all sampling years. Bile fluorescence displayed a gradient of exposure with experimental ponds being elevated over local perch populations. Naphthenic acids decreased in the Bison Pond from approximately 12 mg/L to <4 mg/L while naphthenic acids increased in the Demonstration Pond from 6 mg/L to 12 mg/L due to tailings densification. Temporal changes in naphthenic acid levels, CYP1A activity and bile fluorescent metabolites correlate positively with incidence of disease pathologies whereas all inorganic water quality changes (major ions, pH, metals) were not associated with disease responses. Graphical abstract: Highlights: Yellow perch were stocked into experimental ponds representing situations of oil sands exposure. Water quality and disease incidence in fish were compared between 1995-1997 and 2008–2010. Levels of naphthenic acids, conductivity and pH increased in the pond with underlying tailings. CYP1A activity and bile fluorescent metabolites showed a gradient of oil sands-associated exposure. Incidence of disease pathologies were associated with exposure to oil sands-affected water.